The Canonical Gospels in Michel Henry’s “Philosophy of Christianity”: The Synoptics as a Praeparatio for the Gospel of John - Francisco Martins; Andreas Gonçalves Lind (Religions)
This article explores Michel Henry’s interpretation of the canonical Gospels in his Christian Trilogy. While Henry’s phenomenology emphasizes the immanent self-manifestation of a truth transcending all linguistic mediations, he recognizes the canonical authority of the Gospels as authentic sources of Christ’s words, granting privileged access to that same truth. His surprising focus on Synoptic Gospels, especially in Words of Christ, contrasts with his usual preference for Johannine and Pauline writings. However, his interpretation of the Synoptics tends to uniformize their literary and theological diversity and ignore the narratives and particularities of each Gospel. We suggest that Henry’s hermeneutics is guided less by an exegetical intention than by the principles of his radical phenomenology of life. In short, the article shows the clear risk of eisegetical projection at the core of Henry’s philosophy of Christianity.